An Exploratory Study on E-Waste Reporting: A Review of Annual Reports from Malaysian Public Listed Companies - Azman, Nik Amalena Najebah Nik; Salleh, Sharina Mohd; Hanafi, Wan Noordiana Wan; Ya’acob, Nur Shuhada; Alrazi, Bakhtiar; Yusoff, Haslinda (European Journal of Sustainable Development, 2024)
Electronic waste (e-waste) has emerged as a critical global issue due to the environmental and health impacts. Moreover, a significant portion remains unrecorded and improperly managed. Hence, effective e-waste management is crucial to mitigating associated risks and ensuring environmental sustainability. The current study examined e-waste reporting practices among Malaysian Public Listed Companies (PLCs), assessed PLC commitments to environmental sustainability, and explored the legitimacy theory in understanding e-waste reporting. This study focused on Malaysian PLCs. The sample comprises 114 PLCs distributed across various sectors, such as construction, consumer products and services, energy, financial services, healthcare, and technology, which represented 15% of the total population. A content analysis approach was employed to identify relevant information in annual reports. Subsequently, a categorisation scheme with eight content categories across four dimensions was adapted from previous research to analyse e-waste reporting practices. The findings revealed that the e-waste reporting among PLCs was low as the information was primarily declarative and neutral. Varying commitment levels were also observed across different sectors, which highlighted the communication methods of PLCs on e-waste management practices. The legitimacy theory was applied to appraise the factors contributing to e-waste reporting behaviours. The findings contributed to a deeper understanding of how different industries managed e-waste and valuable insights into the most optimal practices to be adopted across sectors. The study results also underscored the need for standardised reporting frameworks to enhance transparency and corporate responsibility towards environmental sustainability. Keywords: E-waste Reporting, Malaysian Public Listed Companies, Legitimacy Theory, Environmental Sustainability, Content Analysis